2007
DOI: 10.1103/physrevb.75.064404
|View full text |Cite
|
Sign up to set email alerts
|

Charge-switchable molecular magnet and spin blockade of tunneling

Abstract: We analyze a model for a metal-organic complex with redox orbitals centered at both the constituent metal ions and ligands. We focus on the case where electrons added to the molecule go onto the ligands and the charge fluctuations on the metal ions remain small due to the relatively strong Coulomb repulsion. Importantly, if a nonzero spin is present on each metal ion it couples to the intramolecular transfer of the excess electrons between ligand orbitals. We find that around special electron fillings, additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Beyond the issue of control over single-molecule magnetism, is the understanding of coupled molecular magnets or magnetic centers. Apart from spin-blockade effects, expected for large spin molecular ground states [65], the effect of spin-orbit interaction on the exchange coupling between two magnetic centers inside a magnetic double quantum dot is of interest. For instance, the spin-orbit induced Dzyaloshinskii-Moriya or antisymmetric exchange interaction was shown to give rise to a characteristic dependence of the transport on an externally applied magnetic field and the polarizations of magnetic electrodes [66].…”
Section: Complex Excitation Spectra: Vibrations and Spin-orbit Splittingmentioning
confidence: 99%
“…Beyond the issue of control over single-molecule magnetism, is the understanding of coupled molecular magnets or magnetic centers. Apart from spin-blockade effects, expected for large spin molecular ground states [65], the effect of spin-orbit interaction on the exchange coupling between two magnetic centers inside a magnetic double quantum dot is of interest. For instance, the spin-orbit induced Dzyaloshinskii-Moriya or antisymmetric exchange interaction was shown to give rise to a characteristic dependence of the transport on an externally applied magnetic field and the polarizations of magnetic electrodes [66].…”
Section: Complex Excitation Spectra: Vibrations and Spin-orbit Splittingmentioning
confidence: 99%
“…With respect to mesoscopic systems, organic molecules have attracted much interest from the experimental and theoretical aspects, due to their superior performances like flexibility, inexpensive material and production methods, and compatibility with biological systems [4]. However, during the past long time, little progress has been made in the field of organic-based spin polarization, and the realization of spin polarization usually depends on the magnetic properties of the inorganic electrodes [5][6][7]. Recently, it has been reported that electron transport through double-stranded DNA (dsDNA) oligomers has a chance to be spin selective.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a great deal of effort has been paid to study quantum transport through SMMs both theoretically and experimentally [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The experiment of electron transport through the Mn 12 attached with nonmagnetic electrodes has shown that the macroscopic quantum tunneling of the SMM plays an important role due to breaking symmetry [3].…”
Section: Introductionmentioning
confidence: 99%